Identifikasi dan Efektivitas Bakteri Dekomposer Terhadap Limbah Batang daun Jagung untuk Pupuk Organik - Faesal, Faesal; Djaenuddin, Nurasiah; Soenartiningsih, Soenartiningsih (Jurnal Penelitian Pertanian Tanaman Pangan, 2017)
Maize waste is difficult to decompose naturally, therefore needed special treatment to accelerate dissolved of maize waste. Identification and effectivity tested of decomposer bacteria on maize waste for organic fertilizer is one ways to overcome these problem. The research aim to find effective bacteria as decomposer of maize waste as organic fertilizer. Research was conducted in South Sulawesi Indonesia in June to Desember 2013. The first step in this research was collecting soil sample from many natural habitat ie: maize planting site, heap of stem and corn cob, heap of paddy straw or husk, and heap of sorghum stem. The second step where soil sample bring to the Pest and Plant Diseases Laboratory of ICERI for identify decomposer cellulolitic bacteria. We have identified 120 isolate than screened by temperature 50o C and we found of 29 decomposer bacteria by assumption. Furthermore those isolate were tested in vitro 29 sellulolitic bacteria and we found 16 effective sellulolitic bacteria. Than 16 effective sellulolitic bacteria we tested by using stem and leaf of maize in green house and finally found of 6 effective decomposer bacteria, which more effective compared to EM4 as a control. Those isolate decomposer bacteria more effective are: E7.1, E7.3, B7.1 (Bacillus sp), E7.7, H7.1 (Escherichia sp), and C4.1 (Micrococcus sp).